1992
DOI: 10.1007/bf02244831
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation does not alter brain regional benzodiazepine binding site numbers, affinity and coupling in the rat

Abstract: Male Sprague-Dawley rats were differentially housed for 21 days immediately after weaning. Isolated animals showed a selective suppression of exploration of the light side of a two compartment box; spending significantly less time in the light, and making fewer transitions between the light and dark compartments compared to socially reared controls. However, both basal and GABA-stimulated [3H] flunitrazepam binding was unaltered in the frontal cortex, hippocampus, amygdala and cerebellum following social isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
3
3
0
Order By: Relevance
“…Ahmed et al, 1995;Morinan et al, 1992;Vasar et al, 1993). Isolation also influences only initial activity during tests in a novel environment (Gentsch et al, 1982).…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Ahmed et al, 1995;Morinan et al, 1992;Vasar et al, 1993). Isolation also influences only initial activity during tests in a novel environment (Gentsch et al, 1982).…”
Section: Discussionsupporting
confidence: 40%
“…The number of crossings in the peripheral area can measure general activity of rats, and exploration (approaching response to a novel place) can be measured by the number of entries into the center area (Einon & Morgan, 1976;Hall et al, 1997b). Additionally, anxiety, which causes a decrease in exploration especially in phobic places, can be measured by the time of stay in the center area (Morinan, Parker, Rich, Cariuk, & Horton, 1992;.…”
supporting
confidence: 47%
See 1 more Smart Citation
“…percentage open time, [15], [16]) but not others (i.e. those activity-related [12], [13]). In contrast to our findings, it has been reported that individual-housing decreases latency to enter an open arm of the plus-maze [16].…”
Section: Discussionmentioning
confidence: 89%
“…Some reports show that social isolation causes anxiety in rats (Jankowska et al, 1991; Maisonnette et al, 1993; Morinan et al, 1992) while other studies showed no significant effect (Lapiz et al, 2001). In the present study, isolated mice, in both the groups, spent shorter duration in the open arms (Fig.…”
Section: Discussionmentioning
confidence: 98%